A Cationic [60] Fullerene Derivative Reduces Invasion and Migration of HT-29 CRC Cells in Vitro at Dose Free of Significant Effects on Cell Survival - Lucaf`o, Marianna; Pelillo, Chiara; Carini, Marco; Ros, TatianaDa; Prato, Maurizio; Sava, Gianni (Nano-Micro Letters, 2014)
Nanomaterials with unique characteristics exhibit favorable therapeutic and diagnostic properties, implying their enormous potential as biomedical candidates. C60 has been used in gene- and drug-delivery, as imaging agents, and as photosensitizers in cancer therapy. In this study, the influences of a cationic functionalized fullerene on cellular behavior of human colorectal cancer cell line (HT-29) were investigated. Results indicated that HT-29 treated with the studied compound showed a lower sensitivity but a significant impairment in migration and invasion by interfering with the activities of matrix metalloproteinases (MMP-2 and 9). The presence of fullerene also altered the capacity of adhesion-related proteins to perform their activity, thereby inducing dramatically adverse effects on the cell physiological functions such as cell adhesion. Thus, our study suggests that this compound is a new potential anti-metastatic effector and a therapeutic component for malignant colorectal cancer.